Analysis of Determining The Selling Price Using The Time and Material Pricing Method at CV. Abdi Jaya - Bagas Arya Septian; Dedi Mulyadi; Santi Pertiwi Hari Sandi (West Science Business and Management, 2024)
The purpose of this study was to determine the pricing of time and materials in determining the price of painting and welding services set by the Abdi Jaya Motor workshop in determining the appropriate price. The data used in this study are primary and secondary data obtained directly from Abdi Jaya Motor workshop. The analysis used is a quantitative descriptive method that uses time and material prices to calculate the price of painting and welding services. The methods used in this research are (1) direct interviews with stakeholders, (2) direct observation, and (3) data recording. The research results obtained are that pricing using time and material pricing is lower than the price set by CV. Abdi Jaya Motor. The conclusions obtained based on the results of the data analysis that has been carried out are: (1) The total cost of producing one hour of service is IDR 24,783, with the results of the calculation of the price of repair services obtained, namely for painting the body per panel with a standard color of IDR 544,417.64 and IDR 568,109.34 for the red color, while for welding the price per meter is IDR 81,347.16, (2) The mark up charged on materials is 14.1%. The implications of this research are expected to be able to review the use of the time and material pricing method in determining the price of car body repair services, on the grounds of the calculation results, the price of car body painting and welding services is relatively affordable in order to attract the interest of many customers and when using the time and material pricing method, it is expected to make it easier if there are irregularities in finance because financial records are carried out in more detail and precisely.